Szidatitrema yamagutii n. sp. (Digenea: Cyclocoelidae: Ophthalmophaginae) from the bearded barbet, Lybius dubius (Capitionidae), and the white-necked myna, Streptocitta albicollis (Sturnidae), that died at the Audubon Zoo in New Orleans, Louisiana, U.S.A. - Dronen, Norman O.; Craig, Thomas M.; Hammond, Elizabeth E. (Zootaxa, 2006)
Szidatitrema yamagutii n. sp. was found in the air sacs and body cavities of 2 bearded barbets, Lybius dubius, and a white-necked myna, Streptocitta albicollis, that died at the Audubon Zoo, New Orleans, Louisiana between June, 2000 and April, 2005. The new species can be distinguished from Szidatitrema philomachii and Szidatitrema vogeli, the only species currently assigned to this genus, by having a smaller egg size (80–105 by 40–55 compared to 117–126 by 54–72 and 110 by 50, respectively) and the testes of S. yamagutii n. sp. are less obliquely positioned relative to each other. Szidatitrema yamagutii n. sp. further differs from S. philomachii by lacking an oral sucker and having larger testes (anterior testis 405 by 375 compared to 270 by 210; posterior testis 435 by 370 compared to 225 by 210) and from S. vogeli by having a shorter cirrus sac (345 compared to 554) ), smaller testes (anterior testis 405 long compared to 700; posterior testis 435 long compared to 500), a smaller ovary (220–330 wide compared to 400), and a larger postovarian space (approximately 10% of body length compared to 6%). This new species was likely introduced into the Audubon Zoo through the importation of species of Old World birds.